2019
DOI: 10.1097/pcc.0000000000001845
|View full text |Cite
|
Sign up to set email alerts
|

Positive Cumulative Fluid Balance Is Associated With Mortality in Pediatric Acute Respiratory Distress Syndrome in the Setting of Acute Kidney Injury

Abstract: Objective: As acute kidney injury (AKI) and elevated cumulative fluid balance (CFB) commonly co-occur in pediatric ARDS, we aimed to identify risk-factors for their development and evaluate their independent relationships with mortality. We hypothesized that AKI and elevated CFB would

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 56 publications
2
32
1
1
Order By: Relevance
“…Regarding the outcome of AKI, the addition of IL-6 as a covariate to the subgroup adjusted model decreased the Day 1 total FGF23 OR from 1.42 (95% CI 0.95, 2.14; p = 0.09) to 1.26 (95% CI 0.81, 1.96; p = 0.31) ( Table 4 ). In this adjusted model, plasma IL-6 concentrations were independently associated with Day 3 AKI (OR 1.59 [95% CI 1.13, 2.22], p = 0.007), similar to what has been observed in other analyses of this cohort [35]. Given the association between IL-6 and AKI, we performed mediation analysis to quantify the degree to which variation in IL-6 concentrations mediated the FGF23-AKI association.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Regarding the outcome of AKI, the addition of IL-6 as a covariate to the subgroup adjusted model decreased the Day 1 total FGF23 OR from 1.42 (95% CI 0.95, 2.14; p = 0.09) to 1.26 (95% CI 0.81, 1.96; p = 0.31) ( Table 4 ). In this adjusted model, plasma IL-6 concentrations were independently associated with Day 3 AKI (OR 1.59 [95% CI 1.13, 2.22], p = 0.007), similar to what has been observed in other analyses of this cohort [35]. Given the association between IL-6 and AKI, we performed mediation analysis to quantify the degree to which variation in IL-6 concentrations mediated the FGF23-AKI association.…”
Section: Resultssupporting
confidence: 86%
“…Given the presence of partial mediation, these data suggest both inflammation-dependent and inflammation-independent associations between total FGF23 and AKI. Regarding possible inflammation-dependent effects, previous studies have demonstrated that higher circulating IL-6 levels are independently associated with AKI [35, 5355], and that IL-6 may play a role in AKI pathophysiology [56]. Regarding possible inflammation-independent effects, the pathophysiologic mechanisms related to high concentrations of FGF23 fragments remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical studies have reported that FO increases mortality in patients with sepsis [13,23], acute respiratory distress syndrome [9] and AKI [10,11,22]. The Beijing Acute Kidney Injury Trial (BAKIT) group [11] and other researchers [12,24] have considered FO as an accumulation of a fluid balance greater than 10% of the body weight in kilograms and showed that FO was a risk factor for the incidence of AKI.…”
Section: Fluid Administration Is An Integral Component Of the Managemmentioning
confidence: 99%
“…Optimal fluid resuscitation can ensure hemodynamic stability and improve tissue and organ perfusion [1], but ordinary fluid administration may frequently lead to fluid overload (FO) [2,3]. FO is associated with a poor prognosis, including a prolonged length of hospital stay and duration of MV [4], and FO is also related to a higher mortality rate in critically ill patients [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%